Determinants of Decision-making by Law Enforcement Officers - Anna Masian; Oksana Romanenko (Insight: the psychological dimensions of society, 2023)
The article is devoted to the theoretical and empiricalstudy of the problem of decision-making by lawenforcement officers in modern conditions. The purposeof the article is to present and explain the interactionof external and internal decision-making factorsin the professional activity of law enforcement officers.Methods. Theoretical: analysis and generalizationof the results of applied research in the field of decision-making; empirical: complex author’s methodology;data processing methods: methods of primaryand statistical data processing, correlation analysis.The results. On the basis of the analysisof theoretical and applied research in the field of psychologyof decision-making, the directions for conductinga comprehensive study of various components of the decision-making structure, the impact of stress onthe decision-making process, and typical decision-makingscenarios have been determined. Conductingan empirical research made it possible to single out significantdecision-making factors; correlation analysiswas carried out to establish the relationship betweenthem. The interpretation of the relationship betweenthe variables is presented on the basis of a comparativeanalysis with the results of applied foreign studies.Discussion and conclusions. Multidirectional trendsin decision-making in the activities of law enforcementofficers were revealed: readiness for action is combinedwith a tendency to delay the decision under stress,that requires the development of specially developeddecision-making algorithms. An individual’s ability toreformat decision-making scenarios is directly relatedto the tendency to preserve or destroy established attitudes.Making decisions by one process at the expenseof others, or applying other decision-making scenariosinappropriately under certain circumstances,can lead to reduced performance. At the same time,fear of consequences has an inhibitory effect, whichincreases in conditions of uncertainty and institutionallimitations in the system of law enforcement agencies,that necessitates the study of psychological aspectsof the discretionary behavior of police officers, as wellas the use of special programs for law enforcementofficers at the stage of professional training.